On the q-Konhauser biorthogonal polynomials - H. C. Madhekar; V. T. Chamle (International Journal of Mathematics and Mathematical Sciences)
Recently Al-Salam and Verma discussed two polynomial sets {Zn(α)(x,k|q)} and {Yn(α)(x,k|q)} which are biorthogonal on (0,∞) with respect to a continuous or discrete distribution function. For the polynomials Yn(α)(x,k|q) the operational formula is derived.